Visible learning feedback - Hattie, John; Clarke, Shirley (Routledge, Taylor & Francis Group, 2019)
"Visible Learning: Feedback brings together two internationally known educators, combining Hattie's world famous research expertise with Clarke's vast experience of classroom practice and application. Areas covered include the variability of feedback, the importance of surface, deep and transfer contexts, student to teacher feedback, the power of peer feedback and the power of within-lesson feedback. Feedback is arguably the most critical and powerful aspect of teaching and learning and no other book currently available combines research excellence, theory and vast practical expertise in the same way, making this book an essential resource for teachers in any setting, phase or country"--